Analysis of Amyloid-β Pathology Spread in Mouse Models Suggests Spread Is Driven by Spatial Proximity, Not Connectivity - Mezias, Chris; Raj, Ashish (Frontiers in Neurology, 2017)
Abstract. While the spread of some neurodegenerative disease associated proteinopathies, such as tau and -synuclein, are well studied, and clearly implicate transsynaptic pathology transmission, research into the progressive spread of amyloid- pathology has been less clear. In fact, prior analyses of transregional amyloid- pathology spread have implicated both transsynaptic or other intracellular as well as extracellular based transmission mechanisms. We therefore conducted the current meta-analytic analysis to help assess whether spatiotemporal amyloid- pathology development patterns in mouse models, where regional proteinopathy is more directly characterizable than in patients, better fit with transsynaptic or extracellular based theories of pathology spread. We find that, consistently across the datasets used in this study, spatiotemporal amyloid- pathology patterns are more consistent with extracellular based explanations of pathology spread. Furthermore, we find that regional levels of APP in a mouse model are also better correlated with expected pathology patterns based on extracellular, rather than intracellular or transsynaptic spread.